The Influence of the Constructivist Learning Approach on Students' Poetry Writing Ability in the Indonesian Language Subject for Grade X State Senior High School 11 Garut - Nurani, Leni; -, Hidayat; Komara, Endang; Komara, Nandang; -, Helmawati (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to determine the effect of a constructivist learning approach on students' poetry writing skills. The constructivist approach emphasizes that knowledge is actively constructed by students through direct experience and social interaction. The theory underlying this research is the constructivist theory of Jean Piaget and Lev Vygotsky , who highlighted the importance of the processes of assimilation, accommodation, scaffolding , and the zone of of proximal development (ZPD) in building understanding and skills. The method used is a quantitative method with a quasi-informative approach. experiment, using a pretest-posttest design one group design . Data were collected through poetry writing tests before and after the implementation of the constructivist approach. The results showed a significant increase in students' poetry writing skills, with an average score increasing from 49.35 in the pretest to 73.95 in the posttest . In addition, students' writing motivation also increased, as seen from their enthusiasm, active participation, and courage in expressing ideas through poetry. Based on the results of the study, the constructivist learning approach has a positive influence on students' poetry writing skills. This approach not only improves the technical aspects of writing, but also encourages students to think critically, creatively, and reflectively. Therefore, the constructivist approach is recommended as an effective learning strategy in developing writing skills in schools.